Inhibition of cytotoxic fibril formation of α-synuclein and human insulin by Silymarin from the Silybum marianum - Beitollah Moosakhani; Mahshid Taleb; Zahra Mahmoudi Eshkaftaki; Nasser Nikfarjam; Azam Serajian; Mohammad Bagher Shahsavani; Ali Akbar Meratan (PLoS ONE, 2025)
Silymarin (SIL), the extract obtained from the seeds of milk thistle (Silybum marianum), contains several flavonolignans with a broad range of therapeutic properties such as antioxidant, anti-inflammatory, and neuroprotective effects. Despite several studies indicating the neuroprotective effects of SIL in relating to neurodegenerative diseases (NDs), there is no report regarding the anti-amyloidogenic activity and the mechanism of action of SIL in vitro. Here, we have extracted SIL from the seeds of milk thistle (SIL A), followed by investigating its potential, in comparison with SIL purchased from Sigma company (SIL B), in modulating fibrillogenesis and cytotoxicity of human insulin and α-synuclein (α-syn) amyloid fibrils. The obtained results indicated the potency of both SIL A and SIL B in inhibiting the assembly process and related cytotoxicity of both proteins but via different mechanisms, including inhibition of amyloid fibrillation with the appearance of short fibrils for human insulin and redirecting the assembly process of α-syn toward the formation of small globular structures. The higher inhibitory effects of SIL B may be attributed to its higher silybin content, which is responsible for the most biological, including anti-amyloidogenic, activities of SIL B. Nanonization increased the capacity of both SILs to inhibit fibrillation and related cytotoxicity of both proteins. Taken together, these results may suggest SIL A as a potent candidate relating to NDs and highlight nanonization as a promising approach to increase its anti-amyloidogenic properties.